Perspectives in Zebrafish Research - Caterina Mione, Maria; Blader, Patrick; Del Bene, Filippo; Trompouki, Eirini; Henry Bianco, Isaac (Frontiers Media SA, 2020)
In the past decade, a small tropical vertebrate fish, zebrafish, has rapidly gained the interest of research laboratories worldwide as a model system. This topic will provide updated perspectives on all fields of zebrafish research from experts gathering at the 5th Zebrafish Principal Investigators Meeting in Trento, 20-23 March 2018. The community of researchers using zebrafish is rapidly expanding, necessitating a clear plan for how to tackle central questions that remain a challenge in the field and providing inspiration for future studies. This is the aim of the workshop and the Frontiers Research Topic will provide a platform for dissemination of novel ideas arising from this meeting.